2020
DOI: 10.1080/15476286.2020.1812910
|View full text |Cite
|
Sign up to set email alerts
|

Circular ANRIL isoforms switch from repressors to activators of p15/CDKN2B expression during RAF1 oncogene-induced senescence

Abstract: Long non-coding RNAs (ncRNAs) are major regulators of gene expression and cell fate. The INK4 locus encodes the tumour suppressor proteins p15 INK4b , p16 INK4a and p14 ARF required for cell cycle arrest and whose expression increases during senescence. ANRIL is a ncRNA antisense to the p15 gene. In proliferative cells, ANRIL prevents senescence by repressing INK4 genes through the recruitment of Polycomb-group proteins. In models of replicative and RASval12 oncogene-induced senescence (OIS), the expression of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 75 publications
0
20
0
Order By: Relevance
“…The genotype of chromosome 9p21 affect the balance between linear ANRIL and circANRIL levels in vascular smooth muscle cells (VSMCs) and macrophages. Changes in the level of circANRIL regulate cell apoptosis and inflammation responses ( Song et al, 2017 ; Muniz et al, 2021 ; Holdt et al, 2016 ; Congrains et al, 2012b ). Therefore, the effect of high levels of circANRIL, which inhibits cell proliferation and apoptosis in the early stage of atherosclerotic plaque development in human vascular tissues on atherosclerosis is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The genotype of chromosome 9p21 affect the balance between linear ANRIL and circANRIL levels in vascular smooth muscle cells (VSMCs) and macrophages. Changes in the level of circANRIL regulate cell apoptosis and inflammation responses ( Song et al, 2017 ; Muniz et al, 2021 ; Holdt et al, 2016 ; Congrains et al, 2012b ). Therefore, the effect of high levels of circANRIL, which inhibits cell proliferation and apoptosis in the early stage of atherosclerotic plaque development in human vascular tissues on atherosclerosis is controversial.…”
Section: Discussionmentioning
confidence: 99%
“… 41 circRNAs have also been identified as regulators of various pathways that are involved in aging and cellular senescence. 30 , 42 , 43 , 44 Du et al. found that circ-Foxo3 promotes cardiac senescence by interacting with multiple factors associated with stress and senescence responses.…”
Section: Discussionmentioning
confidence: 99%
“…discovered that an isoform of the circular ANRIL could bind to Polycomb proteins and reduce EZH2 occupation on the p15 and p16 promoters, leading to declined H3K27me3. As a result, the expression of ANRIL or its relative levels versus EZH2 determined the expression of these genes, as well as cell senescence 112 . Noteworthily, many lncRNAs are downstream effectors of EZH2, and over 20% of lncRNAs are regulated by PRC2 (Figure 2 A) 113 .…”
Section: Lncrnas Regulate a Dual Role Of Ezh2 In Prc2-dependent Transcriptionmentioning
confidence: 99%